Prediction and Optimization of Compressive Load of a Green Composite Material from Natural Fiber Using Statistical Approach - Patwari, Anayet U; Bhuiyan, S. Alam; Ahsan, Qumrul; Khan, Iftakhar H.; H. Khan, Nihon (International Journal of Integrated Engineering, 2019)
In the area of technological advancement, environmental awareness are always drawing the attention of the scientists for eco-friendly and recyclable products. Different kinds of composite materials are available in the world fabricated from different materials. Natural composite fabricated from natural fiber are attracted the researchers because of their unique characteristics like bio-degradable, availability, non-toxic nature etc. In this study, a new composite materials of epoxy matrix reinforced with three different fillers (banana fiber, jute fiber and jute fabricate bio-degradable polythene) have been prepared by die molding process. Different cylindrical block have been made using different types of fiber size with equal weight ratio and different weight ratio of fiber and epoxy resin. The center composite design protocol along with the response surface method has been adopted for compression testing of composite materials. A quadratic model has been proposed to predict the compressive load of the molded green composite materials within five levels of the two process parameters. Statistical tools are used for best fitting of the developed quadratic model and desirability analysis is coupled with it in order to find out the optimum process condition for which maximum compressive load is achieved. It has been observed that grain size more than 1 mm and the weight ratio between fiber and resin close to 50% shows the better compressive strength for this particular composite material within this experimental limit.